The Influence of Capital Structure, Firm Size, and Profitability on Firm Value: Evidence from Food and Beverage Companies Listed on the Indonesia Stock Exchange (2022-2024) - Supriyanto Supriyanto; Fasya Annisa Maharani; Murti Wijayanti (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the effects of capital structure, firm size, and profitability on firm value among food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research was motivated by the decline in firm value, as reflected in the Price-to-Book ratio, during the research period. The study employed a quantitative method using secondary data obtained from companies’ financial statements. The sampling technique used was purposive sampling, resulting in 114 observations after data transformation. Data analysis was performed using multiple linear regression in IBM SPSS Statistics 26, with classical assumption tests, hypothesis testing, and coefficient of determination tests. The results indicate that capital structure and firm size do not have a significant effect on firm value, whereas profitability has a positive and significant effect. Simultaneously, capital structure, firm size, and profitability significantly affect firm value. Therefore, profitability becomes the most dominant factor in increasing firm value in the food and beverage sub-sector